ASSESSMENT OF THE WILLINGNESS OF THE MANAGEMENT OF CATERING FACILITIES IN VRNJAČKA BANJA TO OFFER LOCAL FOOD - Pršić, Marija; Kalenjuk Pivarski, Bojana; Šmugović, Stefan; Ivanović, Velibor (The Business of Tourism, 2024)
Contemporary trends in tourism, as well as tourist movements in selected destinations, are shaped by various factors. Hospitality establishments that include local food in their offer increase their competitiveness in the market, contributing to a more positive image. The key role in the implementation of local food, as a motive for attracting guests, is played by the readiness and knowledge of the management, which is analyzed through three aspects: organizational climate, culture and the advantages of offering local dishes. The subject of this work is the assessment of the readiness of the management of catering establishments to offer local food. The research is aimed at assessing the readiness of management for innovations aimed at the use of local agricultural, food and gastronomic products, taking into account the characteristics of managers as key actors in deciding on the placement of local products in catering. The study is focused on Vrnjačka Banja, an important spa tourist center of Serbia. The goal of this research is to provide answers to the research questions and assess the readiness of the management to introduce local food in their offer.
Keywords: local food; management; gastronomic tourism; Vrnjacka Banja; gastronomic offer